Anti-ghrelin Spiegelmer inhibits exogenous ghrelin-induced increases in food intake, hoarding, and neural activation, but not food deprivation-induced increases - Teubner, Brett J. W. (American Physiological Society, 2013)
Circulating concentrations of the stomach-derived “hunger-peptide” ghrelin increase in direct proportion to the time since the last meal. Exogenous ghrelin also increases food intake in rodents and humans, suggesting ghrelin may increase post-fast ingestive behaviors. Food intake after food deprivation is increased by laboratory rats and mice, but not by humans (despite dogma to the contrary) or by Siberian hamsters; instead, humans and Siberian hamsters increase food hoarding, suggesting the latter as a model of fasting-induced changes in human ingestive behavior. Exogenous ghrelin markedly increases food hoarding by ad libitum-fed Siberian hamsters similarly to that after food deprivation, indicating sufficiency. Here, we tested the necessity of ghrelin to increase food foraging, food hoarding, and food intake, and neural activation [c-Fos immunoreactivity (c-Fos-ir)] using anti-ghrelin Spiegelmer NOX-B11–2 (SPM), an l-oligonucleotide that specifically binds active ghrelin, inhibiting peptide-receptor interaction. SPM blocked exogenous ghrelin-induced increases in food hoarding the first 2 days after injection, and foraging and food intake at 1–2 h and 2–4 h, respectively, and inhibited hypothalamic c-Fos-ir. SPM given every 24 h across 48-h food deprivation inconsistently inhibited food hoarding after refeeding and c-Fos-ir, similarly to inabilities to do so in laboratory rats and mice. These results suggest that ghrelin may not be necessary for food deprivation-induced foraging and hoarding and neural activation. A possible compensatory response, however, may underlie these findings because SPM treatment led to marked increases in circulating ghrelin concentrations. Collectively, these results show that SPM can block exogenous ghrelin-induced ingestive behaviors, but the necessity of ghrelin for food deprivation-induced ingestive behaviors remains unclear.